Nesiritide in patients hospitalized for acute heart failure: does timing matter? Implication for future acute heart failure trials. (27th January 2016) - Wong, Yee Weng; Mentz, Robert J.; Felker, G.Michael; Ezekowitz, Justin; Pieper, Karen; Heizer, Gretchen; Hasselblad, Vic; Metra, Marco; O'Connor, Christopher M.; Armstrong, Paul W.; Starling, Randall C.; Hernandez, Adrian F.
Abstract : Aims: It remains unclear if early administration of i.v. nesiritide in patients hospitalized with acute heart failure (AHF) is associated with improved clinical outcomes. Methods and results: We analysed data from 7007 patients enrolled in ASCEND‐HF to examine the associations between time to treatment with study medication (nesiritide or placebo) and clinical endpoints: (i) moderate to marked dyspnoea relief on a 7‐point Likert scale at 6 h; (ii) 30‐day all‐cause mortality or re‐hospitalization; and (iii) 30‐day all‐cause mortality. The median time to study drug administration was 16.7 h (25th, 75th percentiles = 6.5, 23.1), with significant regional variation (e.g. median of 13.0 h in Asia‐Pacific vs. 18.4 h in North America). After risk adjustment, each hour delay in study medication after the first 10 h from initial hospital presentation was associated with modestly reduced odds of dyspnoea relief [(adjusted odds ratio (OR) 0.98, 95% confidence interval (CI) 0.98–0.99; P < 0.0001]. Every hour delay in study medication was associated with modestly higher all‐cause mortality or re‐hospitalization (unadjusted OR 1.01, 95% CI 1.01–1.02; P < 0.001) due to pre‐randomization therapies and known predictors of 30‐day outcomes (adjusted P = 0.12). There was no significant association between time to study drug and all‐cause mortality ( P > 0.08). Conclusion: In a large international AHF trial, time to treatment with study medication varied markedly across regions. Earlier administration of study medication was associated with modestly better dyspnoea relief, but not 30‐day clinical outcomes. The association between timing of treatment with study medication and study endpoints may have implications for the interpretation of AHF studies and future trial design.